An efficient compact blazed grating antenna for optical phased arrays - Farheen, Henna; Joshi, Suraj; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Journal of Physics: Photonics)
Phased arrays are vital in communication systems and have received significant interest in the field of optoelectronics and photonics, enabling a wide range of applications such as LiDAR, holography, wireless communication, etc. In this work, we present a blazed grating antenna that is optimized to have upward radiation efficiency as high as 80% with a compact footprint of 3.5 μm × 2 μm at an operational wavelength of 1.55 μm. Our numerical investigations demonstrate that this antenna in a 64 × 64 phased array configuration is capable of producing desired far-field radiation patterns. Additionally, our antenna possesses a low side lobe level of -9.7 dB and a negligible reflection efficiency of under 1%, making it an attractive candidate for integrated optical phased arrays.
Keywords: tet_topic_opticalantenna

European Heritage Label. Selection. Report of the European Panel to the European Commission. 2021

Using academic mathematical knowledge when working on interface tasks–analyses of pre-service teachers’ arguments about rotationally symmetric figures - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Abstract Special tasks for pre-service teachers (PSTs) in university mathematics courses (“interface tasks”) are a common innovation in recent years to overcome the second discontinuity. By this, we mean tasks that are situated by typical everyday challenges of mathematics teaching and in which PSTs must use their mathematical knowledge and skills in a professionally relevant way. In this paper, we analyze answers that PSTs have created to an interface task on symmetry. The PSTs were asked to clarify a student’s question from a mathematical perspective and then give a suitable elementarized answer. We situate these two steps theoretically and reconstruct the mathematical reasoning in PSTs' answers. Through qualitative content analysis, we examined how PSTs justify figures' symmetries from a university mathematics perspective and when responding to the fictitious student. The scenario of a student questioning the existence of 100° rotationally symmetrical figures elicited rich and varied responses, proving suitable for an interface task. We compared PSTs' reasoning related to mathematical clarification with the reasoning related to elementarization. In many cases, this revealed a productive use of course content. An interesting result is that there is no uniform picture as to whether the arguments are more detailed in the mathematical clarification or in the elementarization.

Uncovering Impact of Innovation: Continuous Stakeholder Engagement through Scenario-based Systems Engineering - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Proceedings of the 21st ISCRAM Conference (ISCRAM 2024))
The importance of extreme weather situations is increasing due to their number and, above all, their impact on stakeholders in emergency response. They are characterized by cascading effects with global and local interdependencies. Extreme data must be included as a basis for decision-making. The impact in emergency response depends on diverse, multidisciplinary competencies required to interpret information. Scenarios are used in various forms of preparation: in exercises, but also for the design of information systems and validation. Based on literature, this article brings together different types of scenarios and related work in the field of Model-Based Systems Engineering. Using an exemplary case relating to possible pluvial urban floods, the added value resulting from a focus on the impact of innovative solutions is discussed. It is shown that the use of scenarios helps to make the desired impact assessable for decision-makers in all phases of research and development projects.

Extending the application of simulation from preparedness to response use cases in weather-induced emergencies - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Mensch und Computer 2024 - Workshopband)
Weather-induced emergencies are characterized by underlying weather phenomena, their evolution in time and space as well as their impact on the environment including people, nature and infrastructure. Typically, simulations are used to consider a variety of potential extreme weather scenarios in preparedness phases. Due to required computing power, duration and high efforts in parameterizing such tools are hardly used within response situations. Enhanced simulation models and surrogate models based on machine learning technologies carry potentials to overcome these challenges. An approach is presented that adopts simulation for the case of flooding events. It considers all phases from demand situation in command posts through advanced parameter space exploration to advanced visualization of simulation results in Augmented Reality. Initial evaluation results are presented, complemented by conclusions on incorporated technologies. The results contribute to future adoption of simulation even in time-critical response situations.
Keywords: extreme weather; emergency response; simulation; Augmented Reality

Adopting Generative AI for Literature Reviews: An Epistemological Perspective - Schryen, Guido; Marrone, Mauricio; Yang, Jiaqi (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

A Design Theory for Spontaneous Volunteer Coordination Systems in Disaster Response - Betke, Hans; Sperling, Martina; Schryen, Guido; Sackmann, Stefan (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

EDGE: Evaluation Framework for Logical vs. Subgraph Explanations for Node Classifiers on Knowledge Graphs - Sapkota, Rupesh; Köhler, Dominik; Heindorf, Stefan (Proceedings of the 33rd ACM International Conference on Information and Knowledge Management (CIKM ’24),)

Rezension zu: Jungen als Bildungsgewinner (Michael Richter) - Daniel-Söltenfuß, Desiree (Erziehungswissenschaftliche Revue)

Innovativer Transfer oder Transfer von Innovationen? Transfer im Kontext der Entwicklung von Berufsbildungsinnovationen am Beispiel des InnoVET-Programms - Daniel-Söltenfuß, Desiree (bwp@)

„halb und halb“ – Hybride Edition als Kompromiss? Eine Studie zu Methodik, Möglichkeiten und Grenzen in der hybriden Musikedition am Beispiel der Edition von Ludwig Baumanns „Kantate. Den Gefallenen zum Gedächtnis, den Trauernden zum Trost“ - Ried, Dennis
Vor etwa 20 Jahren haben hybride Editionen in der Musikwissenschaft Einzug gehalten. Es sind in erster Linie Langzeitprojekte mit Laufzeiten von über 15 Jahren (z. ,B. OPERA, RWA, EWK, BAZ-GA) die diese Form der Edition verwenden. Dennoch gibt es kaum Forschungsliteratur zu diesem Thema. Auch die immer wieder verwendete Forschungssoftware "Edirom" hat bislang weder eine ausreichende Dokumentation erfahren noch ist sie ausgiebig diskutiert worden. Zudem fehlt eine kritische Betrachtung des Phänomens Önline-Portal", welches gerade in der Musikphilologie immer häufiger in Erscheinung tritt. Von der Frage ausgehend, ob die hybride Edition ein Kompromiss aus traditioneller und digitaler Edition darstellt, unternimmt Dennis Ried erstmals den Versuch, den Status quo hybrider (Musik-)Editionen zu eruieren, zu dokumentieren und kritisch zu hinterfragen. "Hybrid" wird dabei stets als Zusammenspiel von Änalogem" und "Digitalem" betrachtet. Anders als traditionelle Dissertationsschriften ist diese Arbeit in zwei Teile gegliedert, wovon der erste aus einer exemplarisch angeführten und quasi eigenständigen wissenschaftlich-kritischen Edition besteht. Im zweiten Teil wird diese dann aktiv in die Theoriebildung eingebunden, um methodische Fragen gezielt erörtern zu können. Ergänzt wird die Dissertationsschrift durch eine auf Zenodo publizierte digitale Datensammlung.
Keywords: Musikwissenschaft; Digitale Edition; Musikphilologie

Virtual Reality as a Tool for Monitoring Additive Manufacturing Processes via Digital Shadows - Rupp, Daniel; Kuhlen, Torsten W.; Rarbach, Sven; Wiechel, Dominik; Pottebaum, Jens; Weidemann, Tizia; Tran, Duc Thanh; Day, Robin; Zielinski, Jonas; König, Valentina; Bremer, Jan; Kosche, Thomas; et al. (Proceedings of the GI VR/AR Workshop 2024)
We present a data acquisition and visualization pipeline that allows experts to monitor additive manufacturing processes, in particular laser metal deposition with wire (LMD-w) processes, in immersive virtual reality. Our virtual environment consists of a digital shadow of the LMD-w production site enriched with additional measurement data shown on both static as well as handheld virtual displays. Users can explore the production site by enhanced teleportation capabilities that enable them to change their scale as well as their elevation above the ground plane. In an exploratory user study with 22 participants, we demonstrate that our system is generally suitable for the supervision of LMD-w processes while generating low task load and cybersickness. Therefore, it serves as a first promising step towards the successful application of virtual reality technology in the comparatively young field of additive manufacturing.

Journalismus aus marxistischer Perspektive - Fuchs, Christian (Journalismustheorien)

Wissenschaftsdidaktik als kritische Kommunikationsanalyse
Welchen Zusammenhang haben Kommunikation, Lehre und Wissenschaft? Die Autor*innen denken Ludwig Hubers Idee von Wissenschaftsdidaktik als Analyse der Kommunikation von Wissenschaften weiter. In deskriptiv-kritischer Absicht wird Kommunikation von konkreten Wissenschaften im Kontext der Lehre – spezifischen Lehrtexten, in der Lehre genutzten Forschungstexten und fachlichen Diskursen über Lehre – zum Gegenstand hochschuldidaktischer Beobachtung und Analyse. Die Beiträge aus verschiedenen Disziplinen regen zur kritischen Hinterfragung wissenschaftlicher Praxis an und eröffnen Wissenschaften die Möglichkeit, sich durch die kritische Selbstreflexion ihrer Kommunikation weiterzuentwickeln. Beteiligte Disziplinen sind Biologie, Chemie, Erziehungswissenschaft, Ethik, Geographie, Geschichtswissenschaft, Literaturwissenschaft, Mathematik, Medizin, Physik, Psychologie und Volkswirtschaftslehre.

Action inhibition in a sport-specific paradigm: examining the limits of action control in basketball - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Psychological Research)
Abstract To investigate the point where inappropriate defensive movements can no longer be inhibited and to validate suitable stimulus material for constructing a basketball-specific anticipation-response-inhibition task, two experiments were conducted. In Experiment 1, participants without basketball expertise (N = 25) watched a video of a basketball jump shot and were asked to release the space bar at the point when the ball leaves the player's fingertips (go-trials). In 25% of all trials, the video was stopped prematurely and participants should withhold their finger-lift response (stop-trials). A staircase-tracking algorithm was used to adjust the point-in-time when the jump shot was stopped in a way that participants’ inhibition rate was at 50% (reflecting the so called “point-of-no-return”, PNR). In Experiment 2, the stimulus material was adapted so that stop-trials simulated a pump fake. The PNR in Experiment 1 was located 187 ms and in Experiment 2 177 ms before the point of ball release. Precision performance benefit from practice across blocks and participants delayed their responses after stop-trials in a subsequent go-trial, which reflects strategic post-stop-trial adjustments. Based on the comparable results of previous studies, the given stimulus material is suitable for investigating response inhibition skills in dynamic sport-specific environments.

Disentangling Dialect from Social Bias via Multitask Learning to Improve Fairness - Spliethöver, Maximilian; Menon, Sai Nikhil; Wachsmuth, Henning (Findings of the Association for Computational Linguistics ACL 2024)
Dialects introduce syntactic and lexical variations in language that occur in regional or social groups. Most NLP methods are not sensitive to such variations. This may lead to unfair behavior of the methods, conveying negative bias towards dialect speakers. While previous work has studied dialect-related fairness for aspects like hate speech, other aspects of biased language, such as lewdness, remain fully unexplored. To fill this gap, we investigate performance disparities between dialects in the detection of five aspects of biased language and how to mitigate them. To alleviate bias, we present a multitask learning approach that models dialect language as an auxiliary task to incorporate syntactic and lexical variations. In our experiments with African-American English dialect, we provide empirical evidence that complementing common learning approaches with dialect modeling improves their fairness. Furthermore, the results suggest that multitask learning achieves state-of-the-art performance and helps to detect properties of biased language more reliably.

Multi-Objective Optimization for Sparse Deep Multi-Task Learning - Hotegni, Sedjro Salomon; Berkemeier, Manuel Bastian; Peitz, Sebastian (2024 International Joint Conference on Neural Networks (IJCNN))
Different conflicting optimization criteria arise naturally in various Deep Learning scenarios. These can address different main tasks (i.e., in the setting of Multi-Task Learning), but also main and secondary tasks such as loss minimization versus sparsity. The usual approach is a simple weighting of the criteria, which formally only works in the convex setting. In this paper, we present a Multi-Objective Optimization algorithm using a modified Weighted Chebyshev scalarization for training Deep Neural Networks (DNNs) with respect to several tasks. By employing this scalarization technique, the algorithm can identify all optimal solutions of the original problem while reducing its complexity to a sequence of single-objective problems. The simplified problems are then solved using an Augmented Lagrangian method, enabling the use of popular optimization techniques such as Adam and Stochastic Gradient Descent, while efficaciously handling constraints. Our work aims to address the (economical and also ecological) sustainability issue of DNN models, with a particular focus on Deep Multi-Task models, which are typically designed with a very large number of weights to perform equally well on multiple tasks. Through experiments conducted on two Machine Learning datasets, we demonstrate the possibility of adaptively sparsifying the model during training without significantly impacting its performance, if we are willing to apply task-specific adaptations to the network weights. Code is available at https://github.com/salomonhotegni/MDMTN.

The CHiME-8 DASR Challenge for Generalizable and Array Agnostic Distant Automatic Speech Recognition and Diarization - Cornell, Samuele; Park, Taejin; Huang, Steve; Boeddeker, Christoph; Chang, Xuankai; Maciejewski, Matthew; Wiesner, Matthew; Garcia, Paola; Watanabe, Shinji (arXiv:2407.16447)
This paper presents the CHiME-8 DASR challenge which carries on from the previous edition CHiME-7 DASR (C7DASR) and the past CHiME-6 challenge. It focuses on joint multi-channel distant speech recognition (DASR) and diarization with one or more, possibly heterogeneous, devices. The main goal is to spur research towards meeting transcription approaches that can generalize across arbitrary number of speakers, diverse settings (formal vs. informal conversations), meeting duration, wide-variety of acoustic scenarios and different recording configurations. Novelties with respect to C7DASR include: i) the addition of NOTSOFAR-1, an additional office/corporate meeting scenario, ii) a manually corrected Mixer 6 development set, iii) a new track in which we allow the use of large-language models (LLM) iv) a jury award mechanism to encourage participants to explore also more practical and innovative solutions. To lower the entry barrier for participants, we provide a standalone toolkit for downloading and preparing such datasets as well as performing text normalization and scoring their submissions. Furthermore, this year we also provide two baseline systems, one directly inherited from C7DASR and based on ESPnet and another one developed on NeMo and based on NeMo team submission in last year C7DASR. Baseline system results suggest that the addition of the NOTSOFAR-1 scenario significantly increases the task's difficulty due to its high number of speakers and very short duration.

Selbstinszenierungspraktiken als Weg zu Stärkenorientierung, Selbstbestimmung und Teilhabe – eine Kollegiale Weiterbildung für multiprofessionelle Akteursgruppen im (inklusiven) Übergang Schule-Beruf - Kundisch, Heike; Kremer, H.-Hugo; Otto, Franziska (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Der Beitrag stellt ein Qualifizierungsformat für (multi)professionelle Bildungsakteur*innen zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor. Die Konzeption und Entwicklung des Weiterbildungsformats ist im Rahmen eines Forschungs- und Entwicklungsprojekts für Jugendliche in ausbildungsvorbereitenden Bildungsgängen angesiedelt, die einen besonderen Förderbedarf im Zuge des Übergangs von der Schule in die Berufs- und Arbeitswelt aufweisen. Diese sollen durch offene und kreative Selbstdarstellungs- und Erhebungsformate dabei unterstützt werden, ihre Stärken zu erkennen, zu dokumentieren und sichtbar zu machen, sowie hierüber gleichsam für den Übergang Schule-Beruf gestärkt werden. Wir stellen zunächst den Projektrahmen vor und schärfen in diesem Kontext den Zugang über eine Grundlegung zu Selbstinszenierung sowie deren Potenziale im Kontext der inklusiven Berufsbildung und zur Stärkung der Zielgruppe. Das im Projekt entwickelte Rahmenkonzept bietet eine Orientierung zur standort- respektive bildungsgangbezogenen Anpassung und stellt damit Herausforderungen und einen entsprechenden Qualifizierungsbedarf für Bildungsakteur*innen heraus. Darauf basierend stellen wir die konzeptionellen Grundlagen, die methodische und inhaltliche Ausgestaltung zum Ansatz der ‚Kollegialen Weiterbildung‘ zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor und adressieren u. a. das Zusammenspiel von innovativer Entwicklung, Schärfung von Rollen und Kompetenzentwicklung der Bildungsakteur*innen. Abschließend diskutieren wir die konzeptionellen Entwicklungen und den Implementations- und Transferansatz. Abstract The article presents a qualification format for multi-professional actors in the educational context on the developmental use of 'Selbstinszenierungspraktiken' (which means a combination of practices for self-awareness, self-realisation and self-acceptance in a process which we are developing in our project). The concept and development of the further education format is located within the framework of a research and development project for young people with wide-ranging needs in pre-vocational education units at the transition from school to work. They will be supported in recognizing, documenting and showing their strengths through open and creative self-expression and survey formats, as well as being strengthened for the transition from school to work. First, we present the project framework and clarify the approach by a theoretical grounding of ‚Selbstinszenierung‘ (similar to a combination of self-awareness, self-realisation and self-acceptance) as well as its potentials in the context of inclusive vocational education by strengthening the target group. The developed framework provides a basis for the adaptation of the concept to a specific location or educational programme and highlights challenges and qualification needs for actors in the educational context. We present the conceptual basis, the methodological and content-related design of the collegial training approach on the developmental use of 'Selbstinszenierungspraktiken'. We address the interaction of innovative development, clarification of roles and competence development of actors in the educational context. Finally, we discuss the conceptual developments and the implementation and transfer approach.
Keywords: General Medicine

Weiterbildung als Co-Kreation – Kollegiale Interaktionsräume im Kontext eines Forschungs- und Entwicklungsprojektes zu Selbstinszenierung im Übergang Schule-Beruf - Kundisch, Heike; Otto, Franziska (bwp@ Spezial 21: Trilaterales Doktorandenseminar der Wirtschaftspädagogik Köln, Paderborn und des BIBB – Einblicke in Forschungsarbeiten)